CD44 sensitivity of platelet activation, membrane scrambling and adhesion under high arterial shear rates - Liu, Guilai; Liu, Guoxing; Alzoubi, Kousi; Chatterjee, Madhumita; Walker, Britta; Münzer, Patrick; Luo, Dong; Umbach, Anja T.; Elvira, Bernat; Chen, Hong; Voelkl, Jakob; Föller, Michael; Mak, Tak Z.; Borst, Oliver; Gawaz, Meinrad; Lang, Florian (Thrombosis and Haemostasis, 2016)
CD44 is required for signalling of macrophage migration inhibitory factor (MIF), an anti-apoptotic pro-inflammatory cytokine. MIF is expressed and released from blood platelets, key players in the orchestration of occlusive vascular disease. Nothing is known about a role of CD44 in the regulation of platelet function. The present study thus explored whether CD44 modifies degranulation (P-selectin exposure), integrin activation, caspase activity, phosphatidylserine exposure on the platelet surface, platelet volume, Orai1 protein abundance and cytosolic Ca2+-activity ([Ca2+]i). Platelets from mice lacking CD44 (cd44-/-) were compared to platelets from corresponding wild-type mice (cd44+/+). In resting platelets, P-selectin abundance, αllbβ3 inte-grin activation, caspase-3 activity and phosphatidylserine exposure were negligible in both genotypes and Orai1 protein abundance, [Ca2+]i, and volume were similar in cd44-/- and cd44+/+ platelets. Platelet degranulation and αllbβ3 integrin activation were significantly increased by thrombin (0.02 U/ml), collagen related peptide (CRP, 2 µg/ml and Ca2+-store depletion with thapsigargin (1 µM), effects more pronounced in cd44-/- than in cd44+/+ platelets. Thrombin (0.02 U/ml) increased platelet [Ca2+]i, caspase-3 activity, phosphatidylserine exposure and Orai1 surface abundance, effects again significantly stronger in cd44-/- than in cd44+/+ platelets. Thrombin further decreased forward scatter in cd44-/- and cd44+/+ platelets, an effect which tended to be again more pronounced in cd44-/- than in cd44+/+ platelets. Platelet adhesion and in vitro thrombus formation under high arterial shear rates (1,700 s-1) were significantly augmented in cd44-/- mice. In conclusion, genetic deficiency of CD44 augments activation, apoptosis and prothrombotic potential of platelets.
Keywords: CD44; platelet activation; cytosolic Ca2+ concentration; phosphatidylserine translocation; thrombus formation